Women's Health Leadership to Enhance Community Health Workers as Change Agents. Issue 3 (May 2016) - Ingram, Maia; Chang, Jean; Kunz, Susan; Piper, Rosie; de Zapien, Jill Guernsey; Strawder, Kay
Objectives . A community health worker (CHW) is a frontline public health worker who is a trusted member of and/or has an unusually close understanding of the community served. While natural leadership may incline individuals to the CHW profession, they do not always have skills to address broad social issues. We describe evaluation of the Women's Health Leadership Institute (WHLI), a 3-year training initiative to increase the capacity of CHWs as change agents. Methods . Pre-/postquestionnaires measured the confidence of 254 participants in mastering WHLI leadership competencies. In-depth interviews with CHW participants 6 to 9 months after the training documented application of WHLI competencies in the community. A national CHW survey measured the extent to which WHLI graduates used leadership skills that resulted in concrete changes to benefit community members. Multivariate logistic regressions controlling for covariates compared WHLI graduates' leadership skills to the national sample. Results . Participants reported statistically significant pre-/postimprovements in all competencies. Interviewees credited WHLI with increasing their capacity to listen to others, create partnerships, and initiate efforts to address community needs. Compared to a national CHW sample, WHLI participants were more likely to engage community members in attending public meetings and organizing events. These activities led to community members taking action on an issue and a concrete policy change. Conclusions . Leadership training can increase the ability of experienced CHWs to address underlying issues related to community health across different types of organizational affiliations and job responsibilities.